Lowered Sintering Temperature on Synthesis of La9.33Si6O26 (LSO) – La0.8Sr0.2Ga0.8Mg0.2O2.55 (LSGM) Electrolyte Composite and the Electrical Performance on La0.7Ca0.3MnO3 (LCM) Cathode - Yoga Trianzar Malik; Atiek Rostika Noviyanti; Dani Gustaman Syarif (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2018)
Solid oxide fuel cell (SOFC) is the device that can convert chemical energy into electricity with highest efficiency among other fuel cell. La9.33Si6O26 (LSO) is the potential electrolyte at intermediate operation temperature SOFC. Low ionic conductivity of lanthanum silicate-based electrolyte will lead into bad electrical performance on lanthanum manganite-based anode. In this study, LSO was combine with La0.8Sr0.2Ga0.8Mg0.2O2.55 (LSGM) electrolyte by using conventional solid state reaction to enhance the electrical performance of LSO on LCM cathode. However, pre-requisite high sintering temperature on preparation of LSO-LSGM composite will lead into phase transition phase of LSGM that may affect in decreasing the electrical performance. This study resulted that lowered sintering temperature from its ideal temperature still give an improved electrical performance of LCM/LSO-LSGM/LCM symmetrical cell. The ASR value is 0.14 Ω.cm2 which much lower than its analogous symmetrical cell, LSM/LSO/LSM that was reported before.